1985
DOI: 10.1016/s0006-3495(85)83954-0
|View full text |Cite
|
Sign up to set email alerts
|

Ionic channels with conformational substates

Abstract: Recent studies of protein dynamics suggest that ionic channels can assume many conformational substates. Long-lived substates have been directly observed in single-channel current records. In many cases, however, the lifetimes of conformational states will be far below the theoretical limit of time resolution of single-channel experiments. The existence of such hidden substates may strongly influence the observable (time-averaged) properties of a channel, such as the concentration dependence of conductance. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Lev et al have concluded that the relaxation rates of some conformational degrees of freedom are comparable or smaller than the frequency of ion jumps in the channel. As Ciani (1984) and Läuger (1985) indicated, there is an appreciable difference between fast and slow conformational motions. Läuger observed that the fast conformational degrees of freedom; that is, the motions whose characteristic times are small compared to the time of an ion jump over the barrier, manage to accommodate themselves to the ion and their role amounts to making the ion "heavier" just as the electron becomes heavier in a crystal when it interacts with lattice vibrations (the polaron effect).…”
Section: Bilinear Models Of Biological Membranesmentioning
confidence: 99%
“…Lev et al have concluded that the relaxation rates of some conformational degrees of freedom are comparable or smaller than the frequency of ion jumps in the channel. As Ciani (1984) and Läuger (1985) indicated, there is an appreciable difference between fast and slow conformational motions. Läuger observed that the fast conformational degrees of freedom; that is, the motions whose characteristic times are small compared to the time of an ion jump over the barrier, manage to accommodate themselves to the ion and their role amounts to making the ion "heavier" just as the electron becomes heavier in a crystal when it interacts with lattice vibrations (the polaron effect).…”
Section: Bilinear Models Of Biological Membranesmentioning
confidence: 99%
“…2), so that the fluxes of N and S are completely coupled. For a discussion of the more general case of arbitrary coupling ratio, see Ciani (1984) andL/iuger (1985). We further assume (as before) that the binding/unbinding reactions at the interface are always in equilibrium.…”
Section: Cn Csmentioning
confidence: 99%
“…A large Cl-conductance is important to stabilize the resting membrane potential, as mammalian muscles with reduced Cl-conductance become hyperexcitable and produce trains of action potentials characteristic of myotonia (Adrian & Bryant, 1974). Using the patch-clamp recording technique (Hamill, Marty, Neher, Sakmann & Sigworth, 1981) to explore for channels that might underlie the resting Cl-conductance, we have observed three Cl--selective channels in cultured rat skeletal muscle (Blatz & Magleby, 1983, 1985. One of these channels has a large conductance of 430 pS (symmetrical 143 mM-KCl) but is unlikely to contribute significantly to resting Cl-conductance, because it is closed at resting membrane potentials.…”
Section: Introductionmentioning
confidence: 99%